A Review of Methods for Detection of Hepatozoon Infection in Carnivores and Arthropod Vectors - Modrý, David; Beck, Relja; Hrazdilová, Kristýna; Baneth, Gad (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2017)
Vector-borne protists of the genus Hepatozoon belong to the apicomplexan suborder Adeleorina. The taxonomy of Hepatozoon is unsettled and different phylogenetic clades probably represent evolutionary units deserving the status of separate genera. Throughout our review, we focus on the monophyletic assemblage of Hepatozoon spp. from carnivores, classified as Hepatozoon sensu stricto that includes important pathogens of domestic and free-ranging canine and feline hosts. We provide an overview of diagnostic methods and approaches from classical detection in biological materials, through serological tests to nucleic acid amplification tests (NAATs). Critical review of used primers for the 18S rDNA is provided, together with information on individual primer pairs. Extension of used NAATs target to cover also mitochondrial genes is suggested as a key step in understanding the diversity and molecular epidemiology of Hepatozoon infections in mammals.
Keywords: Arthropod Vectors; Hepatozoon; Eucoccidiida; diagnostics; PCR; Polymerase Chain Reaction; polymerázová řetězová reakce; Carnivora; Animals; Protozoan Infections, Animal; členovci - vektory; protozoální infekce zvířat; zvířata